Term-Concept Relationship in an Information Retrieval Thesaurtis - Seetharama, S. (Journal of Information and Knowledge, 1976)
Concept representation in thesauri, especially the representation of compound concepts, has been studied. The criteria and relative advantages in representing a compound concept either as a precombined descriptor or as a combination of elemental descriptors, are discussed with illustrative examples taken from Medical Subject Headings (MeSH) of the National Library of Medicine.